PROGRAM BIMBINGAN KELOMPOK UNTUK MENINGKATKAN LITERASI INFORMASI SEKSUAL MELALUI QUANTUM LEARNING - Azni Nurul Fauzia, Azni Nurul Fauzia (2022)
One of the sexual developments of children towards adolescents is that they begin to have an interest in sexual information. The main sources of sexual information on children are peers and various media. The limitations of parents and educators in monitoring access to children's sexual information make it important for children to be equipped with sexual information literacy. Sexual information literacy is a set of skills needed to identify information needs and sources, access information, evaluate, and use and communicate effectively, efficiently and ethically on sexual information. The quantum learning strategy as a fun learning process and exploring various intelligences and learning styles is believed to be able to help students improve sexual information literacy. The research was carried out with the aim of obtaining empirical data describing the sexual information literacy of sixth graders, obtaining the formulation of a quantum learning program to improve information literacy of sixth graders, and obtaining empirical data on the effectiveness of quantum learning in improving the ability of sixth graders in sexual information literacy. The research was conducted on the sixth grade students of SDN 137 Cijerokaso Bandung. The research method is a descriptive method with a quasi-experimental research design. The group of participants involved in the experimental group amounted to twelve people. Sexual information literacy of students using sexual information literacy instruments. Participants took the test twice, before being given treatment (pretest) and after being given treatment (posttest). The results showed that the sexual information literacy profile of class VI students at SDN 137 Cijerokaso was in the medium category and students who took part in the quantum learning program in general experienced an increase, but the results of statistical tests showed that quantum learning guidance was not effective in increasing the sexual information literacy of participants. grade VI SDN 137 Cijerokaso.